Sheep development program in Egypt - Elshennawy, M. (1995)
Sheep population in Egypt is about 3 million. The three major Egyptian sheep breeds are Barki, Ossimi and Rhamani, Representing 65% of the total population. They are well adapted to local conditions, small to medium size and have a twinning rate ranging from 1.05 to 1.30. A trial for improving prolificacy was carried out through crossbreeding with Finnsheep. On station, results indicated significantly higher prolificacy for crossbreds but on-farm trials with ¼ finnsheep, ¾ local ewes showed no significant difference in either prolificacy or economic return. Although characterization of those local breeds has been established and genetic parameters estimated, no effective selection programme has been started.